Genotoxic Effects of Etoposide, Bleomycin, and Ethyl Methanesulfonate on Cultured CHO Cells: Analysis by GC-MS/MS and Comet Assay. (30th July 2020) - Atha, Donald H.; Coskun, Erdem; Erdem, Onur; Tona, Alessandro; Reipa, Vytas; Nelson, Bryant C.
Abstract : To evaluate methods for analysis of genotoxic effects on mammalian cell lines, we tested the effect of three common genotoxic agents on Chinese hamster ovary (CHO) cells by single-cell gel electrophoresis (comet assay) and gas chromatography-tandem mass spectrometry (GC-MS/MS). Suspension-grown CHO cells were separately incubated with etoposide, bleomycin, and ethyl methanesulfonate and analyzed by an alkaline comet assay and GC-MS/MS. Although DNA strand breaks were detected by the comet assay after treatment with all three agents, GC-MS/MS could only detect DNA nucleobase lesions oxidatively induced by bleomycin. This demonstrates that although GC-MS/MS has limitations in detection of genotoxic effects, it can be used for selected chemical genotoxins that contribute to oxidizing processes. The comet assay, used in combination with GC-MS/MS, can be a more useful approach to screen a wide range of chemical genotoxins as well as to monitor other DNA-damaging factors.